Detection and Extraction of Transients for Audio Coding - Niemeyer, Oliver; Edler, Bernd (120th AES Convention, 2006)
An algorithm for the detection and extraction of transient signal components is presented. It is based on the detection of sharp onsets of the signal power in time direction of the complex time frequency domain. Afterwards the detected transients are extracted in the corresponding MDCT spectrum. The audio signal containing only the extracted transients is synthesized using the inverse MDCT. In an audio coding application this transient signal and a resulting residual signal can be coded separately using specifically optimized coders. One approach of such an audio coding scheme using an MDCT based coder for the transient signal is also presented.<br